Analysis of mechanisms of underfill in full penetration laser welding of thick stainless steel with a 10 kW fiber laser. (1st January 2018) - Zhang, Mingjun; Zhang, Zheng; Tang, Kun; Mao, Cong; Hu, Yongle; Chen, Genyu
Graphical abstract: Highlights: The downward flow on the front keyhole wall is a key driver for top underfill. The fluctuation of the rear keyhole wall leads to a periodic top underfill. The backward liquid flow and root hump cause top underfill with a blind keyhole. Top underfill and bottom undercut are formed with an open keyhole. Abstract: With the aim to explore the formation mechanisms of surface underfill, full penetration laser welding of thick stainless steel was conducted, with the use of a 10 kW fiber laser. A modified "sandwich" specimen was used, so as to directly observe the dynamic behaviors of the keyhole, vapor plume, and melt pool with the formation of underfills. On the basis of the experimental investigations, the formation mechanisms of the underfills at the top surface and bottom surface were analyzed. The results show that the downward flow of the molten metal caused by the recoil momentum is a crucial driver for formation of the underfill on the top surface. At full penetration of the melt, a deep underfill with a periodic wide–narrow–wide serrated pattern is formed on the top surface of the weld owing to the periodic fluctuation of the rear keyhole wall. At full penetration of the keyhole, the formation of a deep underfill on the top surface of the weld and undercut on the bottom surface of the weld is presented with massive direct melt loss from the weld pool.